A preparation method, product and application of perovskite microcrystals
Perovskite microcrystals are prepared by anti-solvent-assisted inversion crystallization method, which solves the problems of high defect state density and poor stability of perovskite films in the prior art, and achieves low defect state density and full absorption of perovskite microcrystals Characteristics improve the stability and photoelectric performance of perovskite solar cells.
Patent Information
- Application Number
- CN202410239247.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-04
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-03-04
AI Technical Summary
In the prior art, when preparing the light absorption layer thin film of perovskite solar cells, the obtained perovskite crystal thin film has high defect state density and poor stability, resulting in poor operating stability of the battery, limiting the commercialization of perovskite solar cells. .
The anti-solvent-assisted inversion crystallization method is used to quickly prepare high-quality hexahedral perovskite microcrystals at lower temperatures. By controlling the crystallization conditions and using an appropriate solvent system, the defective state density of the microcrystals is reduced.
The prepared perovskite microcrystals have a low defect state density (1010-1013cm-3), maintain full absorption within the visible light range of 300-850nm, and significantly improve stability and photoelectric properties, making them suitable for large-area and commercial preparation. perovskite optoelectronic devices functional layer.
Smart Images

Figure CN118109906B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic device preparation, and in particular to a preparation method, product and application of perovskite microcrystals. Background Art
[0002] Organic-inorganic hybrid perovskite has been widely used and studied due to its excellent optoelectronic properties, including long exciton and charge diffusion lengths, high extinction coefficients, and low-temperature processability. It is a good material for the light-absorbing layer of solar cells (PSCs). Previous studies have focused on the preparation of large-grained light-absorbing layer films using in-situ crystallization techniques using a one-step or two-step method. Currently, the power conversion efficiency (PCE) of perovskite solar cells using this in-situ crystallization method to prepare the light-absorbing layer has exceeded 26%. However, the perovskite crystal films obtained by these methods have a narrow light absorption range and poor stability, resulting in poor operating stability of this type of cell, which has become a major obstacle to the commercial application of perovskite solar cells.
[0003] The existing technology for preparing perovskite thin film crystals is to use a one-step method or a two-step method to prepare a polycrystalline film. The microcrystal defect density obtained by this technology is very large. 15 -10 19 cm -3 The stability is very poor. Scientists have used various methods to passivate and modify the surface defects of crystals and films, but none of them can effectively reduce the defect state density, so that the stability of the battery has not been effectively improved for a long time, which has become a major scientific and technological problem in this field. At the same time, the absorption spectrum of this polycrystalline film shows a significant downward trend after 500nm, which is not conducive to the absorption of the entire visible light band and the utilization of spectral energy by solar cells. The process of preparing the active layer of solar cells by in-situ spin coating crystallization is not suitable for the preparation of large-area films.
[0004] Therefore, providing a method for preparing perovskite microcrystals to reduce the defect state density of perovskite microcrystals and improve their absorption spectrum range is of great significance in the field of photovoltaic device preparation technology. Summary of the invention
[0005] Based on the above content, the present invention provides a preparation method, product and application of perovskite microcrystals.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention is a perovskite microcrystal with a tetragonal crystal structure; a defect state density of 10 10 -10 13 cm -3The general structural formula is ABX3, wherein A is at least one of methylamine MA, methylamine FA, and Cs; B is Pb; and X is at least one of I, Br, and Cl.
[0008] A second technical solution of the present invention is a method for preparing the above-mentioned perovskite microcrystals, comprising the following steps:
[0009] Dissolving PbX2, AX and hexadecyltrimethylammonium bromide in a good solvent to obtain a precursor solution;
[0010] adding an anti-solvent to the precursor solution, filtering, and heating the obtained filtrate to obtain the perovskite microcrystals;
[0011] A in the AX is at least one of MA, FA, and Cs, and X is at least one of I, Br, and Cl.
[0012] A third technical solution of the present invention is a perovskite solar cell, wherein the light absorbing layer material includes the above-mentioned perovskite microcrystals.
[0013] A fourth technical solution of the present invention is a flexible photoelectric detection device, the raw materials of which include the above-mentioned perovskite microcrystals.
[0014] A fifth technical solution of the present invention is an electroluminescent device, the raw materials of which include the above-mentioned perovskite microcrystals.
[0015] The present invention discloses the following technical effects:
[0016] The perovskite microcrystal ABX3 (A = MA, FA, Cs and a mixture of two or three components; B = Pb; X = I, Br, Cl) of the present invention has a tetragonal crystal structure and a low defect state density (10 10 -10 13 cm -3 ), maintains full absorption in the visible light range of 300-850nm, has good stability, and has good photoelectric properties.
[0017] The raw materials of the invention are cheap and readily available, the preparation process is simple, and the invention is suitable for large-scale and commercial preparation.
[0018] The present invention uses the anti-solvent-assisted inversion crystallization method to quickly prepare high-quality hexahedral perovskite microcrystals at a relatively low temperature. The micron-sized single crystals have a tetragonal crystal structure, and their production cycle is much shorter than that of bulk single crystals. In addition, the raw material utilization rate is higher, and they are more suitable for industrial production. Compared with thin films, microcrystals have a narrower band gap; at the same time, microcrystals have better air stability, thermal stability, and wet stability than thin films. In addition, microcrystals have a wider absorption range than thin films, achieving full absorption in the visible light range. The above properties make perovskite microcrystals a strong candidate for the functional layer of large-area, commercialized perovskite optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 These are SEM photographs of MAPbI3 microcrystals prepared in Examples 1 and 2 of the present invention; wherein, the left picture is a SEM photograph of MAPbI3 microcrystals prepared in Example 1, and the right picture is a SEM photograph of MAPbI3 microcrystals prepared in Example 2.
[0021] Figure 2 This is the X-ray diffraction pattern of MAPbI3 microcrystals prepared in Example 1 of the present invention.
[0022] Figure 3 UV-visible-near-infrared absorption spectra of the MAPbI3 microcrystals prepared in Example 1 of the present invention and the MAPbI3 perovskite film prepared in Comparative Example 1.
[0023] Figure 4 This is the relationship between PbI2 concentration and MAPbI3 yield when the CTAB concentration is 0.02 mmol / mL and the PbI2 and MAI concentration ratio is 1:2 in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] The "%" described in the present invention, unless otherwise specified, refers to mass percentage.
[0030] The first aspect of the present invention provides a perovskite microcrystal having a tetragonal crystal structure; a defect state density of 10 10 -10 13 cm -3 The general structural formula is ABX3, wherein A is at least one of methylamine MA, methylamine, and Cs; B is Pb; and X is at least one of I, Br, and Cl.
[0031] A second aspect of the present invention provides a method for preparing the above-mentioned perovskite microcrystals, comprising the following steps:
[0032] Dissolving PbX2, AX and hexadecyltrimethylammonium bromide in a good solvent to obtain a precursor solution;
[0033] adding an anti-solvent to the precursor solution, filtering, and heating the obtained filtrate to obtain the perovskite microcrystals;
[0034] A in the AX is at least one of MA, FA, and Cs, and X is at least one of I, Br, and Cl.
[0035] In a preferred embodiment of the present invention, the concentration of PbI2 in the precursor solution is 0.3 mmol / mL; the concentration of AX in the precursor solution is 0.6 mmol / mL; by adding excess AX, the colloid particle size is reduced, which can increase the crystallization sites that promote crystal precipitation, thereby reducing the crystal particle size and accelerating the crystallization rate. Therefore, the present invention limits the concentration of AX in the precursor solution to twice the concentration of PbI2.
[0036] The concentration of cetyltrimethylammonium bromide (CTAB) in the precursor solution is 0-0.02 mmol / mL.
[0037] The crystal particle size of the perovskite microcrystals is related to the concentration of CTAB in the precursor solution. When the CTAB concentration in the precursor solution is 0-0.02mmol / mL, as the CTAB concentration increases, the crystal particle size gradually decreases. When the CTAB concentration is 0.02mmol / mL, the crystal particle size prepared is about 0.5-1.5μm; when the CTAB concentration in the precursor solution exceeds 0.02mmol / mL, as the CTAB concentration increases, there are too many crystallization sites, which is easy to produce dependent growth, and it is not easy to form hexahedral crystals, and the crystal quality is poor; when CTAB is not added to the precursor solution, the crystal particle size of the prepared perovskite microcrystals is about 100μm;
[0038] In a preferred embodiment of the present invention, the good solvent is γ-valerolactone. The present invention also verifies other good solvents such as N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone and γ-butyrolactone, and the results show that the effects are not as good as γ-valerolactone.
[0039] In a preferred embodiment of the present invention, the anti-solvent is anisole. The present invention also verifies that other anti-solvents such as cyclohexane, n-hexane, toluene, o-xylene, ether, iodobenzene, dichloromethane, chlorobenzene, isopropanol, n-propanol, methyl acetate, ethanol, n-butanol, isobutanol and ethyl acetate have inferior effects.
[0040] The present invention uses a good solvent and an anti-solvent as a mixed solvent, adopts an anti-solvent-assisted inversion crystallization technology, uses PbX3 (X = I, Br and Cl) and ammonium halides (A = MA, FA or Cs, etc.) as raw materials, controls the crystallization conditions, and can prepare a large number of highly stable, wide-absorption hexahedral perovskite microcrystals (0.5-100 microns). The environmental stability and spectral absorption characteristics of the perovskite microcrystals prepared by the method of the present invention are systematically characterized. The results show that the hexahedral perovskite microcrystals prepared by the method of the present invention not only have excellent stability, but also show strong absorption in the range of 300-850nm, and can be used as a non-in-situ preparation of the light absorption layer material of the perovskite solar cell, solve the problem of the operation stability of the device, and promote the practical application of the perovskite solar cell. At the same time, it can also be used as the preparation of the photoelectric conversion functional layer of flexible photoelectric detection devices and electroluminescent devices. The present invention provides a feasible and effective preparation strategy for the non-in-situ preparation of perovskite microcrystal photoelectric conversion functional layer materials.
[0041] In a preferred embodiment of the present invention, the anti-solvent is added dropwise; the anti-solvent is added to the precursor solution until saturated.
[0042] In a preferred embodiment of the present invention, the heating temperature is 95-120° C. and the heating time is no more than 1 minute; and after the heating, the steps of filtration, rinsing and drying are also included in sequence.
[0043] As the heating temperature increases, the particle size of the perovskite microcrystals decreases. Taking MAPbI3 as an example, the average particle size is 1.6 μm at 95°C, and the average particle size is 1 μm at 120°C. When the heating temperature is higher than 120°C, crystallization is too fast, the crystal shape is irregular, and the quality is poor. When the heating temperature is higher than 150°C, the precursor solution is unstable, easy to deteriorate, and it is difficult to generate crystals; when the temperature is lower than 95°C, crystallization is slow, the crystal particle size monodispersity is poor, and it will not crystallize when it is lower than 60°C. Therefore, the preferred heating temperature of the present invention is 95-120°C.
[0044] In a preferred embodiment of the present invention, after adding the anti-solvent to the precursor solution and before filtering, the step of stirring for 1 hour is also included.
[0045] In a preferred embodiment of the present invention, when the AX is MAI, the preparation method comprises the following steps: slowly adding HI solution to a slightly excess CH3NH2 ethanol solution under ice-water bath conditions, removing the solvent after the reaction is complete, dissolving the precipitated crystals in anhydrous ethanol, recrystallizing three times with ethyl acetate and drying to obtain the MAI. AX obtained by other routes, such as commercial routes, is also applicable to the present invention.
[0046] The micro-scale perovskite single crystal prepared by the method of the present invention has a long carrier diffusion length and a low defect state density (10 10 -10 13 cm -3 ) characteristics, maintaining full absorption in the visible light range of 300-850nm, and having room for further improving energy utilization efficiency. The high-stability perovskite microcrystals of the present invention can be used as a highly potential light-absorbing layer material preparation technology for perovskite solar cells.
[0047] The present invention provides a process suitable for large-scale, commercial preparation of light-absorbing functional layer materials of perovskite solar cell devices. The process is suitable for non-in-situ preparation of functional layer materials of perovskite photoelectric devices.
[0048] A third aspect of the present invention provides a perovskite solar cell, wherein the light absorbing layer material comprises the above-mentioned perovskite microcrystals.
[0049] A fourth aspect of the present invention provides a flexible photoelectric detection device, the raw material of which includes the above-mentioned perovskite microcrystals.
[0050] A fifth aspect of the present invention provides an electroluminescent device, the raw materials of which include the above-mentioned perovskite microcrystals.
[0051] The present invention will be further described below by way of examples.
[0052] Example 1 (MAPbI3)
[0053] Step 1, synthesis of methylamine iodine (MAI): Slowly add 47% HI solution (the volume ratio of CH3NH2 ethanol solution to HI solution is 7:6) to 30% CH3NH2 ethanol solution in an ice-water bath. After the reaction is complete, remove the solvent using a rotary evaporator, dissolve the precipitated white crystals in anhydrous ethanol, recrystallize three times with ethyl acetate, and dry in a vacuum oven at 60°C for 12 hours to obtain MAI white powder.
[0054] Step 2, preparation of MAPbI3 microcrystals: prepare a γ-valerolactone (GVL) precursor solution with a PbI2 concentration of 0.3 mmol / mL, an MAI concentration of 0.6 mmol / mL, and a cetyltrimethylammonium bromide (CTAB) concentration of 0.02 mmol / mL, stir until completely dissolved, slowly add anisole (ANS) to saturation, stir for 1 hour (the stirring speed depends on the amount of raw materials, the stirring speed of 1 mL of precursor solution should be 300 rpm), filter, place the filtrate on a 95°C heating table, and black crystals precipitate after about 1 minute. Filter by suction, rinse with dichloromethane, and dry in a 60°C vacuum oven for 6 hours to obtain MAPbI3 microcrystals.
[0055] The defect state density of MAPbI3 microcrystals prepared in this example is 4.6×10 13 cm -3 ; The average particle size is 10μm.
[0056] In Example 1, the CTAB concentration was 0.02 mmol / mL and the MAI and PbI2 concentration ratio was maintained at 2:1. The concentration of PbI2 in the precursor solution was adjusted to find the corresponding concentration with the highest MAPbI3 yield. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that when the PbI2 concentration is 0.3 mmol / mL (at this time the MAI concentration is 0.6 mmol / mL), the corresponding yield is the highest, that is, the raw material utilization rate is the highest.
[0057] Example 2
[0058] The only difference from Example 1 is that the concentration of hexadecyltrimethylammonium bromide (CTAB) in step 2 is 0.01 mmol / mL; the remaining steps and parameters are the same as those in Example 1.
[0059] The defect state density of MAPbI3 microcrystals prepared in this example is 7.8×10 13 cm -3 ; The average particle size is 2.3μm.
[0060] The surface morphology of the MAPbI3 microcrystalline powders prepared in Examples 1 and 2 was characterized by scanning electron microscopy (SEM). Figure 1 As shown; wherein the left figure is a SEM photograph of MAPbI3 microcrystals prepared in Example 1, and the right figure is a SEM photograph of MAPbI3 microcrystals prepared in Example 2; Figure 1 As shown in the middle left figure, after magnification 5000 times, the MAPbI3 microcrystals prepared in Example 1 can be clearly seen. The crystals are hexahedral, regular in shape and well dispersed, with almost no agglomeration. Most of the crystals are 1-2μm in size, with an average particle size of 1.6μm. It is known that the carrier diffusion length of MAPbI3 single crystals is 175+25μm, which is much higher than the crystallite size. Therefore, the regularity of the grain size and shape of the MAPbI3 microcrystals prepared in Example 1 creates the possibility for their non-in-situ preparation and application in solar cells. Figure 1 As shown in the middle right figure, if the added CTAB concentration is 0.01 mmol / mL, the particle size of the obtained MAPbI3 microcrystals is about 10 μm.
[0061] The MAPbI3 microcrystalline powder prepared in Example 1 was characterized by X-ray diffraction. Figure 2 As shown in the XRD diagram, it is clearly visible that MAPbI3 microcrystals have no peaks at 2θ angles of 10.9° (MAI characteristic peak) and 11.8° (PbI2 characteristic peak), indicating that the raw material reaction is complete. The microcrystalline powder is well consistent with the standard MAPbI3 absorption peak, with the main peaks located at about 14° and 28°, corresponding to its (002) and (110) crystal planes, respectively, indicating that it has a tetragonal structure. The double peak split at 28.5° corresponding to its (200) crystal plane also proves that it is a tetragonal phase.
[0062] Comparative Example 1 (Preparation of MAPbI3 perovskite film by conventional method)
[0063] 1.5 mol / L lead iodide and 1.5 mol / L methylamine hydroiodide were added to a mixed solvent of 800 μL N,N'-dimethylformamide and 200 μL dimethyl sulfoxide and stirred for 30 min under an inert gas atmosphere until dissolved to obtain a precursor solution. The perovskite precursor solution was dropped onto the prepared substrate and spin-coated at 6000 rpm. After 25 s, 100 μL of anti-solvent (anisole) was quickly dropped and annealed at 100°C for 1 h to obtain a perovskite film.
[0064] The stability of the MAPbI3 microcrystals prepared in Example 1 and the MAPbI3 perovskite film prepared in Comparative Example 1 was characterized. The air stability, thermal stability and moisture stability of the MAPbI3 microcrystals prepared in Example 1 were better than those of the MAPbI3 perovskite film prepared in Comparative Example 1 by conventional methods.
[0065] The absorption characterization of the MAPbI3 microcrystals prepared in Example 1 and the MAPbI3 perovskite film prepared by conventional methods in Comparative Example 1 is shown in the following figure: Figure 3 As shown (in the figure, the directly prepared microcrystals represent the MAPbI3 microcrystals prepared in Example 1; the single crystal ground powder represents the bulk single crystal prepared by the conventional method of Comparative Example 1; the polycrystalline film represents the MAPbI3 perovskite film prepared by the conventional method of Comparative Example 1). Through the tangent and the vertical axis of the curve, it can be calculated that this microcrystalline powder is a direct bandgap semiconductor. The absorption spectrum shows that the ultraviolet absorption curves of MAPbI3 microcrystals and single crystals are almost the same. The absorption band edge of the film is around 800nm, while the absorption band edge of the microcrystals and single crystals is around 850nm, and the absorption peak of the film drops significantly at 550nm. MAPbI3 microcrystals are similar to single crystals and can achieve absorption of the entire visible light band, increasing the absorption and utilization of energy under the bandgap, thereby increasing the theoretical upper limit of the short-circuit current density (JSC) and power conversion efficiency (PCE) of the PSC.
[0066] The present invention uses γ-valerolactone (GVL) and anti-solvent ANS as a mixed solvent, and uses anti-solvent-assisted inversion crystallization. It uses non-high-purity raw materials to quickly (crystallization process is about 1 minute) and prepare a large amount of high-quality ABX3 (A = MA, FA, Cs and a mixture of two or three components; B = Pb; X = I, Br, Cl) perovskite microcrystals. The stability characterization results show that the obtained hexahedral perovskite microcrystals not only have obvious stability advantages over polycrystalline films, but also have a wider absorption spectrum range, and the crystal size of the perovskite microcrystals is controllable within 500nm-100μm. This provides an effective strategy for crystal preparation and non-in-situ preparation of functional layers to improve the photoelectric conversion efficiency of perovskite solar cells and promote the commercial application of perovskite solar cells.
[0067] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A non-in-situ preparation method of regular hexahedral perovskite microcrystals, characterized in that: The following steps are involved: Dissolving PbX2, AX and hexadecyltrimethylammonium bromide in a good solvent to obtain a precursor solution; adding an anti-solvent to the precursor solution, filtering, and heating the obtained filtrate to obtain the perovskite microcrystals; A in the AX is at least one of MA, FA, and Cs, and X is at least one of I, Br, and Cl; The concentration of hexadecyltrimethylammonium bromide in the precursor solution is 0-0.02mmol / mL; The heating temperature is 95-120°C and the heating time is no more than 1 minute; The concentration of PbI2 in the precursor solution is 0.3 mmol / mL; the concentration of AX in the precursor solution is 0.6 mmol / mL; The good solvent is at least one of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, γ-butyrolactone and γ-valerolactone; The anti-solvent is at least one of cyclohexane, n-hexane, toluene, o-xylene, ether, anisole, iodobenzene, dichloromethane, chlorobenzene, isopropanol, n-propanol, methyl acetate, ethanol, n-butanol, isobutanol and ethyl acetate; The perovskite microcrystal is a micron-sized single crystal with a tetragonal crystal structure.
2. The non-in-situ preparation method of regular hexahedral perovskite microcrystals according to claim 1, characterized in that: The anti-solvent is added dropwise; the anti-solvent is added to the precursor solution until saturated.
3. The non-in-situ preparation method of regular hexahedral perovskite microcrystals according to claim 1, characterized in that: After the heating, the method further comprises the steps of suction filtration, rinsing and drying.
4. A regular hexahedral perovskite microcrystal prepared by the non-in-situ preparation method according to any one of claims 1 to 3, characterized in that: It is a single crystal with a tetragonal crystal structure; the defect state density is 10 10 -10 13 cm -3 ; The general structural formula is ABX3, wherein A is at least one of MA, FA, and Cs; B is Pb; and X is at least one of I, Br, and Cl.
5. A perovskite solar cell, characterized in that: The light absorbing layer material includes the regular hexahedral perovskite microcrystals as described in claim 4.
6. A flexible photoelectric detection device, characterized in that: The raw materials include the regular hexahedral perovskite microcrystals as described in claim 4.
7. An electroluminescent device, characterized in that: The raw materials include the regular hexahedral perovskite microcrystals as described in claim 4.
Citation Information
Patent Citations
Method for rapid preparation of large-area perovskite crystals
CN105350078A
Photovoltaic material with thin layer perovskite structure and its preparation method and application
CN108198942A
Preparation method of perovskite material powder
CN113845428A
Alpha-FAPbI3 crystal, preparation method thereof and perovskite solar cell
CN117305968A